2019
DOI: 10.1186/s43094-019-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, anti-inflammatory and anticoagulant activities of three Thymus species grown in southeastern Morocco

Abstract: Background: Thyme has been used for centuries in southeastern Morocco to treat a wide range of diseases such as inflammation disorders. The aim of the current study is to examine and to compare in vitro the anti-inflammatory, antioxidant, and anticoagulant activities of three thyme species grown in southeastern Morocco. Results: Data showed that all studied species possess an important antioxidant activity: Thymus atlanticus (IC 50 = 16.59 μg/mL), Thymus zygis (IC 50 = 15.43 μg/mL), and Thymus satureioides (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…Free radical scavenging was determined by 1,1-diphenyl 1-2-picryl-hydrazyl (DPPH) assay [43]. For the measurement of antioxidant activity, 1 mL of plant extracts (10,20,40,60,80, 100 μg/mL) was mixed with 3 mL of the DPPH solution of 100 mM concentration. The reaction mixtures were incubated for 30 min in dark and absorbance was recorded at 517 nm using a UV-visible spectrophotometer.…”
Section: In-vitro Dpph and Abts Assay For The Determination Of Antioxmentioning
confidence: 99%
See 2 more Smart Citations
“…Free radical scavenging was determined by 1,1-diphenyl 1-2-picryl-hydrazyl (DPPH) assay [43]. For the measurement of antioxidant activity, 1 mL of plant extracts (10,20,40,60,80, 100 μg/mL) was mixed with 3 mL of the DPPH solution of 100 mM concentration. The reaction mixtures were incubated for 30 min in dark and absorbance was recorded at 517 nm using a UV-visible spectrophotometer.…”
Section: In-vitro Dpph and Abts Assay For The Determination Of Antioxmentioning
confidence: 99%
“…In addition, the 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) cation decolorization assay was also performed for the evaluation of antioxidant potential of the plant extracts by using standard procedures followed by the previous investigators slight modifications [44]. An aliquot of 1 mL of plant extract (10,20,40,60,80, 100 μg/mL) was mixed with 3 mL of ABTS working solution and incubated for 10 min in dark. The absorbance was taken at 734 nm.…”
Section: In-vitro Dpph and Abts Assay For The Determination Of Antioxmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was reported that the aqueous extract of T. atlanticus possesses high total phenolic content and exhibited a potent anti-inflammatory effect in animal models of inflammation and inhibits blood coagulation ex vivo and in vivo [12,13]. In addition, the aqueous extract of this plant showed potent in vitro antioxidant activity, but, to our knowledge, its antioxidant activity in vivo has not yet been studied [5,13,14]. A preliminary screening of some ymus species from Morocco for hypolipidemic activity indicated that T. atlanticus showed possible hypolipidemic effects in a rat model [5].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors disclosed a greater antioxidant ability of these polar solvent extracts in comparison to non-polar ones [56]. Different results were described for aqueous extracts of Thymus atlanticus, T. zygis and Thymus satureioides based on ABTS •+ scavenging assay, which corresponded to about 7.5-8.5 times those of the standard ascorbic acid [62].…”
Section: Antioxidant Activitymentioning
confidence: 93%